O professor do ensino regular: seu processo de formação, qualificação e sua atuação com estudantes deficientes visuais - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
In modern societies, education becames an universal right, requiring teachers‟ skills and special abilities. In the particular case of teachers working in public inclusive schools of Manaus, dealing with blind and low vision students, difficulties are great, due to a vast variety of restraints, mainly on the area of knowledge. This matter have aroused a lot of researches, since those students are rightfully embraced by Brazilian Constitution. The State is therefore compelled to put forward the acquisition of skills and formation in order to give to these teachers the access to basic resources applied to this kind of teaching. Among them, we underscore Braille system (method of reading and writing used by sightless people), basic notions of Sorobã (method used for mathematical calculation) and all the other resources used as imperative tools in the teaching and learning process at the classroom. The main aim of this research was to inquire teachers‟ formation and familiarity with didactic material that can enable them to help blind and low vision students at classroom. Applied methodology was book and field research. As tools of research, recorded half structured interviews with teachers and blind students were used. This research was highly important because pinpointed serious problems concerning the formation of teachers destined to instruct and train blind and low vision young people. Thus, ways can be appointed on the field of new researches and works in this area.
Keywords: Estudantes Cegos; Estudantes com baixa visão; Recursos Didáticos Adaptados; CIÊNCIAS HUMANAS: EDUCAÇÃO: ENSINO-APRENDIZAGEM